The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/eqe.3468
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale field testing of geotechnical seismic isolation of structures using gravel‐rubber mixtures

Abstract: We present the results of a large-scale experimental campaign performed on the prototype structure of EuroProteas in Thessaloniki, Greece, to assess the effectiveness of gravel-rubber mixture (GRM) layers underneath shallow foundations as a means of geotechnical seismic isolation (GSI). We found that the geotechnical seismic isolation of structures is optimized by increasing the rubber content of the soil rubber mixture up to 30% per mixture weight. Although the effectiveness of the GSI systems has been invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…Compared to pure sands, the results from these studies showed an improvement of damping ratio associated with a decrease in shear modulus. Large scale tests showed the effectiveness as a means of geotechnical seismic isolation (Pitilakis et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to pure sands, the results from these studies showed an improvement of damping ratio associated with a decrease in shear modulus. Large scale tests showed the effectiveness as a means of geotechnical seismic isolation (Pitilakis et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the past one and a half decades, numerical simulations and analytical modelling have been conducted by various researchers to demonstrate the effectiveness of GSI systems (Tsang et al 2009(Tsang et al , 2012aPitilakis et al 2015;Anbazhagan et al 2015;Abdullah and Hazarika 2016;Brunet et al 2016;Dhanya et al 2020;Forcellini and Alzabeebee 2022). Experimental testing and field measurement have also been performed to confirm the isolation mechanism and to evaluate their performance (Kaneko et al 2013;Nikitas et al 2014;Nappa et al 2016;Tsiavos et al 2019;Tsang et al 2021;Pitilakis et al 2021). It comes to the stage when appropriate design models, procedures and guidelines are needed for systematic design in real applications (Tsang and Pitilakis 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the first large-scale field experimental study of the dynamic response of the EuroProteas prototype structure founded on GRM layers was performed (Pitilakis et al 2021). The experimental findings showed that a thin GRM layer with a height of 0.50 m, including 30% rubber content per mixture weight, could effectively isolate the structure from the foundation soil.…”
Section: Introductionmentioning
confidence: 99%